2016
DOI: 10.5612/slavicreview.75.1.52
|View full text |Cite
|
Sign up to set email alerts
|

A Struggle for the Soviet Future: The Birth of Scientific Forecasting in the Soviet Union

Abstract: This article analyzes the development of Soviet scientific future studies after World War II, arguing that the field's theory and methods undermined the certainty of the communist future and laid the foundations for a new Soviet governmentality that acknowledged the intrinsic uncertainty of future development. The emphasis on uncertainty—but also the need for more data that could freely circulate between different branches of government and hence more transparency (glasnost')—called for radical revisions to So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…There is a large literature on the RAND Corporation. Literature on IIASA is still small despite some important recent publications (Rindzevičiūtė, 2010, 2015, 2016; Schwartz, 2014). Thus in what follows, analysis of RAND will be concise and rely only on secondary sources.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large literature on the RAND Corporation. Literature on IIASA is still small despite some important recent publications (Rindzevičiūtė, 2010, 2015, 2016; Schwartz, 2014). Thus in what follows, analysis of RAND will be concise and rely only on secondary sources.…”
Section: Introductionmentioning
confidence: 99%
“…Delphi has only rarely entered the radar range of historians of science and, if it has, the process of its development has been addressed in passing. The more prominent focus of studies touching upon the history of Delphi has been devoted to the development of futurology in general, and the publication of Delphi is understood as a milestone in the establishment of the field (Andersson, 2012; Tolon, 2012; Rindzevičiūtė, 2016). The history of political gaming is comparatively better researched than the history of Delphi, with the basic facts established and many important arguments made (Ghamari Tabrizi, 2000; Bessner, 2014, 2015; Dayé, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Adam Leeds has demonstrated that the field had powerful military roots in the USSR, leading to the development of programmes for rocketry, nuclear research, and air defence systems (Leeds, 2016). Eglė Rindzevičiūtė’s research traces the impact of cybernetic thought on systems modelling and the use of projective analytics (Rindzevičiūtė, 2015a, 2015b, 2016). Arguing against the prevailing opinion that Soviet computers were derivative and lagged behind their Western counterparts, Ksenia Tatarchenko’s research has exposed the extent of the Soviet computerization efforts conducted in the 1970s and 1980s (Tatarchenko, 2013, 2016).…”
mentioning
confidence: 99%